The Saccharomyces cerevisiae STE14 gene encodes a methyltransferase that mediates C-terminal methylation of a-factor and RAS proteins. - Hrycyna, C A (1991)
Post-translational processing of a distinct group of proteins and polypeptides, including the a-factor mating pheromone and RAS proteins of Saccharomyces cerevisiae, results in the formation of a modified C-terminal cysteine that is S-isoprenylated and alpha-methyl esterified. We have shown previously that a membrane-associated enzymatic activity in yeast can mediate in vitro methylation of an isoprenylated peptide substrate and that this methyltransferase activity is absent in ste14 mutants. We demonstrate here that STE14 is the structural gene for this enzyme by expression of its product as a fusion protein in Escherichia coli, an organism in which this activity is lacking. We also show that a-factor, RAS1 and RAS2 are physiological methyl-accepting substrates for this enzyme by demonstrating that these proteins are not methylated in a ste14 null mutant. It is notable that cells lacking STE14 methyltransferase activity exhibit no detectable impairment of RAS function or cell viability. However, we did observe a kinetic delay in the rate of RAS2 maturation and a slight decrease in the amount of membrane localized RAS2. Thus, methylation does not appear to be essential for RAS2 maturation or localization, but the lack of methylation can have subtle effects on the efficiency of these processes.